Studies of the resonance structure in D0→Kπ[minus-plus]π±π±π[minus-plus] decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (The European physical journal. C, Particles and fields, 2018)
Amplitude models are constructed to describe the resonance structure of D0→K−π+π+π−D0→K−π+π+π−{D^{0}→ K^{-}π ^{+}π ^{+}π ^{-}} and D0→K+π−π−π+D0→K+π−π−π+{D^{0} → K^{+}π ^{-}π ^{-}π ^{+}} decays using pp collision data collected at centre-of-mass energies of 7 and 8 TeV with the LHCb experiment, corresponding to an integrated luminosity of 3.0 fb−1fb−1fb^{-1}. The largest contributions to both decay amplitudes are found to come from axial resonances, with decay modes D0→a1(1260)+K−D0→a1(1260)+K−D^{0} → a_1(1260)^{+} K^{-} and D0→K1(1270/1400)+π−D0→K1(1270/1400)+π−D^{0} → K_1(1270/1400)^{+} π ^{-} being prominent in D0→K−π+π+π−D0→K−π+π+π−{D^{0}→ K^{-}π ^{+}π ^{+}π ^{-}} and D0→K+π−π−π+D0→K+π−π−π+D^{0}→ K^{+}π ^{-}π ^{-}π ^{+}, respectively. Precise measurements of the lineshape parameters and couplings of the a1(1260)+a1(1260)+a_1(1260)^{+}, K1(1270)−K1(1270)−K_1(1270)^{-} and K(1460)−K(1460)−K(1460)^{-} resonances are made, and a quasi model-independent study of the K(1460)−K(1460)−K(1460)^{-} resonance is performed. The coherence factor of the decays is calculated from the amplitude models to be RK3π=0.459±0.010(stat)±0.012(syst)±0.020(model)RK3π=0.459±0.010(stat)±0.012(syst)±0.020(model)R_{K3π } = 0.459± 0.010\,(stat) ± 0.012\,(syst) ± 0.020\,(model), which is consistent with direct measurements. These models will be useful in future measurements of the unitary-triangle angle γγγ and studies of charm mixing and CPCPC\!P violation.
Im Titel wird "pi" als griechischer Buchstabe dargestellt
Im Titel ist die Ziffer "0" hochgestellt
Im Titel sind die Zeichen "plus-minus" und "minus-plus"hochgestellt
LHCb collaboration: R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, F. Dordei, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, A. Piucci, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]
Gesehen am 13.06.2019